2022
DOI: 10.1080/17470919.2022.2083228
|View full text |Cite
|
Sign up to set email alerts
|

Neural network involvement for religious experiences in worship measured by EEG microstate analysis

Abstract: To date, not much is known about large-scale brain activation patterns in religious states of mind and previous studies have not set an emphasis on experience. The present study investigated the phenomenon of religious experiences through microstate analysis, and it was the first neurocognitive research to tackle the dimension of experience directly. Hence, a total of 60 evangelical Christians participated in an experiment where they were asked to engage in worship and try to connect with God. With a bar slide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 120 publications
1
3
0
Order By: Relevance
“…These findings add interesting information to the discovery that, in part, the auditory as well as the default mode network, but most poignantly the salience network, appear to be implicated in such experiences [64]. The next section briefly discusses the relevance of the temporal cortex in regard to the present findings concerning religious experiences.…”
Section: The Present Findingssupporting
confidence: 58%
See 1 more Smart Citation
“…These findings add interesting information to the discovery that, in part, the auditory as well as the default mode network, but most poignantly the salience network, appear to be implicated in such experiences [64]. The next section briefly discusses the relevance of the temporal cortex in regard to the present findings concerning religious experiences.…”
Section: The Present Findingssupporting
confidence: 58%
“…A previous publication on the same population used microstate analyses to disentangle the involved neural networks in these experiences [64]. It was shown that microstate (MS) class 1 (the auditory network) showed a significant association with the average rating values of the religious experience based on its duration, contribution, and mean global field power (GFP) of the microstate.…”
Section: On An Exploratory Notementioning
confidence: 99%
“…Third , microstate analysis can examine if different socio-affective states involve different neural network dynamics, as evidenced by unique changes to microstate features. For example, researchers have analyzed continuous EEG data recorded while participants are processing socio-affective information, such as watching emotional videos (e.g., Chen et al 2021 ; Hu et al 2022 , 2023 ; Liu et al 2023 ) or engaging in worship (Walter and Koenig 2022 ). For example, Hu et al ( 2023 ) examined archival EEG data in which the original authors manipulated emotional states with the presentation of music videos.…”
Section: Applications Of Eeg Microstatesmentioning
confidence: 99%
“…Second, EEG studies in laboratory settings found changes in the parietal association cortex during prayer and religious chanting (Dobrakowski et al, 2020;Walter & Koenig, 2022).…”
Section: Brain Circuitry For Sensing Godmentioning
confidence: 99%